A Hybrid Pythagorean Fuzzy MCDM Approach for Evaluating Supplier Resilience Capability in The Food Packaging Industry - Boyacı, Ali Ihsan; Akman, Gülşen; Maden, Ayça; Alkan, Atakan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Resilience capability in supplier evaluation has increasingly emerged as a critical issue in recent years, highlighted by events such as the COVID-19 pandemic and the Russian-Ukrainian conflict, which have underscored the need for suppliers to be adaptable and robust in the face of various challenges. Accordingly, this study focuses on assessing supplier resilience capability in the food packaging manufacturing industry. The resilience capability concept is defined as a three-dimensional construct based on absorptive capability, response capability and recovery capability for specifically food packaging manufacturing industry. An integrated approach combining the Analytical Hierarchy Process and Weighted Aggregates Sum Product Assessment methods under Interval Valued Pythagorean Fuzzy Set is proposed for evaluating and ranking the suppliers based on their resilience capability. The results of the study revealed that redundancy has the highest rank among other criteria, followed by situational awareness, recovery efficiency, contingency planning, agility, supply chain collaboration, knowledge management, supply chain visibility and correct risk management decisions. At the end of the study, a sensitivity analysis is also performed to demonstrate the robustness and reliability of the decision-making process for assessing and selecting the most resilient supplier in the food packaging manufacturing industry.